Tazemetostat for patients with relapsed or refractory follicular lymphoma: an open-label, single-arm, multicentre, phase 2 trial. Issue 11 (November 2020) - Morschhauser, Franck; Tilly, Hervé; Chaidos, Aristeidis; McKay, Pamela; Phillips, Tycel; Assouline, Sarit; Batlevi, Connie Lee; Campbell, Phillip; Ribrag, Vincent; Damaj, Gandhi Laurent; Dickinson, Michael; Jurczak, Wojciech; et al.
Summary: Background: Activating mutations of EZH2, an epigenetic regulator, are present in approximately 20% of patients with follicular lymphoma. We investigated the activity and safety of tazemetostat, a first-in-class, oral EZH2 inhibitor, in patients with follicular lymphoma. Methods: This study was an open-label, single-arm, phase 2 trial done at 38 clinics or hospitals in France, the UK, Australia, Canada, Poland, Italy, Ukraine, Germany, and the USA. Eligible patients were adults (≥18 years) with histologically confirmed follicular lymphoma (grade 1, 2, 3a, or 3b) that had relapsed or was refractory to two or more systemic therapies, had an Eastern Cooperative Oncology Group performance status of 0–2, and had sufficient tumour tissue for central testing of EZH2 mutation status. Patients were categorised by EZH2 status: mutant ( EZH2 mut ) or wild-type ( EZH2 WT ). Patients received 800 mg of tazemetostat orally twice per day in continuous 28-day cycles. The primary endpoint was objective response rate based on the 2007 International Working Group criteria for non-Hodgkin lymphoma, assessed by an independent radiology committee. Activity and safety analyses were done in patients who received one dose or more of tazemetostat. This study is registered with ClinicalTrials.gov, NCT01897571, and follow-up is ongoing. Findings: Between July 9, 2015, and May 24, 2019, 99 patients (45 in the EZH2 mut cohort and 54 in the EZH2 WT cohort) were enrolled in the study. At data cutoff for the analysis (Aug 9, 2019), the median follow-up was 22·0 months (IQR 12·0–26·7) for the EZH2 mut cohort and 35·9 months (24·9–40·5) for the EZH2 WT cohort. The objective response rate was 69% (95% CI 53–82; 31 of 45 patients) in the EZH2 mut cohort and 35% (23–49; 19 of 54 patients) in the EZH2 WT cohort. Median duration of response was 10·9 months (95% CI 7·2–not estimable [NE]) in the EZH2 mut cohort and 13·0 months (5·6–NE) in the EZH2 WT cohort; median progression-free survival was 13·8 months (10·7–22·0) and 11·1 months (3·7–14·6). Among all 99 patients, treatment-related grade 3 or worse adverse events included thrombocytopenia (three [3%]), neutropenia (three [3%]), and anaemia (two [2%]). Serious treatment-related adverse events were reported in four (4%) of 99 patients. There were no treatment-related deaths. Interpretation: Tazemetostat monotherapy showed clinically meaningful, durable responses and was generally well tolerated in heavily pretreated patients with relapsed or refractory follicular lymphoma. Tazemetostat is a novel treatment for patients with follicular lymphoma. Funding: Epizyme.